Digital accessibility: An analysis of homepages of Federal Education Institutions of Brazil - Arenhardt, Daniel Luís; Franchi, Tatiane Stefanel; Costa, Vânia Medianeira Flores; Grohmann, Márcia Zampieri (Education Policy Analysis Archives, 2017)
For people with disabilities to have their right to access to information guaranteed, it is essential that the basic premises of digital accessibility are implemented on homepages. This question is even more relevant when related to government websites. This study checked the adequacy of electronic sites of Federal Institutions of Education of Brazil for digital accessibility standards established by the Accessibility Model of Electronic Government (eMAG). The results demonstrate a low adherence to these standards, even the standardized elements of accessibility that, by force of law, should be implemented in all electronic portals of government in the country. This demonstrates that a significant portion of citizens has not been respected, on equal terms, in terms of their right of access to digital information in academic and university environments, which should promote citizenship and create opportunities an education quality for all.